Overuse injuries in running: do complex analyses help our understanding? - Hamill, J.; Haddad, J. M.; van Emmerik, R. E. A. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The purpose of this paper is to discuss the change in focus in biomechanics from relatively simple analysis techniques to more complex techniques. Overuse injuries, linked to rearfoot motion, will be used as an example. In the early development of biomechanical techniques, the angle magnitudes were presented to suggest the mechanisms of overuse injuries. Later, coupling rearfoot motion with actions of the knee became commonplace. In these analyses, the timing and ratios of the angular movements were expressed. However, none of these measures provided a sufficient explanation for injury mechanisms. New techniques, derived from dynamical systems theory, have provided a more salient explanation of the overuse injury mechanism through assessing the role of variability in movement coordination.